Mapping the landscape of tandem repeat variability by targeted long read single molecule sequencing in familial X-linked intellectual disability - Alena Zablotskaya; Hilde Van Esch; Kevin J. Verstrepen; Guy Froyen; Joris R. Vermeesch (BMC, 2018)
Abstract Background The etiology of more than half of all patients with X-linked intellectual disability remains elusive, despite array-based comparative genomic hybridization, whole exome or genome sequencing. Since short read massive parallel sequencing approaches do not allow the detection of larger tandem repeat expansions, we hypothesized that such expansions could be a hidden cause of X-linked intellectual disability. Methods We selectively captured over 1800 tandem repeats on the X chromosome and characterized them by long read single molecule sequencing in 3 families with idiopathic X-linked intellectual disability. Results In male DNA samples, full tandem repeat length sequences were obtained for 88-93% of the targets and up to 99.6% of the repeats with a moderate guanine-cytosine content. Read length and analysis pipeline allow to detect cases of > 900 bp tandem repeat expansion. In one family, one repeat expansion co-occurs with down-regulation of the neighboring MIR222 gene. This gene has previously been implicated in intellectual disability and is apparently linked to FMR1 and NEFH overexpression associated with neurological disorders. Conclusions This study demonstrates the power of single molecule sequencing to measure tandem repeat lengths and detect expansions, and suggests that tandem repeat mutations may be a hidden cause of X-linked intellectual disability.